Industrial technological advance and the employment demand for China's labour force-Micro evidence from labour hiring in companies. - Jianmin Liu; Yifeng Shen; Wenye Fan; Xiya Wu (PLoS ONE)
Technological advance in industry has complexity, divisibility, systematicity and market selectivity, and companies may generate technological investment expansion and form technological job demand, which may also lead to the occupation of company resources and trigger the replacement of the original jobs. This paper empirically examines the impact of technological advance in industry on the labour employment demand of companies by taking Chinese A-share listed companies as research samples from 2008 to 2022, and finds that: overall technological advance in industry has a suppressive effect on the labour employment demand of companies; The heterogeneity test shows that industrial technological advancement mainly produces inhibitory effects on the labour employment of low-education level employees and production sectors, while it produces incentive effects on the labour employment of high-education level employees and non-production sectors Industrial technological advancement mainly produces job substitution and destructive effects on the labour employment of low-education level employees and production sectors, while it produces incentive effects on the labour employment of high-education level employees and non-production sectors. Mechanism test shows that industrial technological advancement has incentive effects such as technology investment expansion effect and industry chain conduction effect, and also produces inhibitory effects such as enterprise resource occupation effect and employment delay effect. This paper extends the research on the impact of industrial technological advances on the labour employment demand of companies, and provides empirical evidence and policy insights for rationally arranging industrial structural transformation and labour employment decisions of companies in the context of 'stable employment'.